Digital Economic Transactions in Online Purchase: A Study on Social Media Accounts - Ningrum, Ifa Khoiria; Skenoma, Yudha Prosto; Lukiyanto, Kukuh; Ruspitasari, Widi Dewi; Kusuma, Yoseph Benny (KnE Social Sciences, 2024)
Indonesia has great potential for development in the digital economy, but the behavior of social media users has not yet had an impact on it. The purpose of this study was to explore the behavior of social media users in conducting digital economic transactions. The methodusedwasdescriptive qualitative, with eight subjects selected by purposive sampling by prioritizing the credibility of the informant. The results showed that the development of the digital economy was supported by existing technological developments. However, the behavior of social media users is still diverse, some have a positive influence, and some have a negative influence, so there is a need for government intervention in providing a platform, direction, and also supervision in conducting digital translation. Wider public awareness is also needed to improve the digital economy in a more positive direction. Keywords: digital economy, social media, user behavior, transactions